Estimation of Calcitonin Hormone Levels and its Relation with Tyrosine Kinase Enzyme in Thyroid Cancer Iraqi Patients - R. Abdul Hamza, May; A. Hassan, Firas (Al-Nahrain Journal of Science, 2025)
Medullary thyroid cancer accounts for 5% of all cases of thyroid cancer. It develops from the C-cells of the thyroid. Thus, in addition to its destructive impact on our health, cancer also significantly increases the overall healthcare burden. C-cells manufacture the hormone calcitonin, which plays a somewhat modest part in the process of bone development as well as blood calcium levels. That is because it holds the role of a poor substitute excreted if the thyroid is removed, the effect of calcitonin is weaker than that of thyroid hormone. Luckily, serum calcitonin concentrations that are higher than normal can help make a diagnosis and find out about a thyroid cancer recurrence. In contrast to almost all other thyroid type cancers, medullary thyroid cancer does not assimilate RAI and so the best way of saving the patient’s life is to have the surgery done just in time when the tumour has not yet spread over the body. The greatest risk factor for medullary thyroid cancer is the occurrence of medullary thyroid cancer or MEN syndrome (multiple endocrine neoplasia syndromes) in families, up to 20% of cases carry a genetic flaw. Among other things, the patient screening for the eponymous mutation of the RET proto-oncogene should be given first priority. There are two forms of MEN syndrome. MEN 2A when the tumours develop in the medulla of the thyroid, adrenal and parathyroid glands. MEN 2B when it contains medullary thyroid carcinoma, pheochromocytoma, and multiple ganglioneuromas of the autonomic nervous system.